Surgical management of Staphylococcus capitis prosthetic valve infective endocarditis: Retrospective review of a 10-year single center experience and review of the literature. Issue 11 (November 2020) - Tchana-Sato, Vincent; Hans, Gregory; Frippiat, Frederic; Zekhnini, Ines; Dulgheru, Raluca; Lavigne, Jean P.; Defraigne, Jean O.
Abstract: Background: Staphylococcus capitis ( S. capitis ) is a subtype of coagulase-negative staphylococci and a commensal of the skin of the human scalp and forehead. S. capitis has been occasionally reported in infective endocarditis and rarely in prosthetic valve endocarditis (PVE). The purpose of this report is to present the clinical course and the surgical management of a series of four patients with S. capitis PVE. Methods: The medical records of 190 adult patients with a definite diagnosis of infective endocarditis by the Duke modified criteria and who underwent surgery at our center between January 2008 and December 2018 were retrospectively reviewed. Results: There were four cases of S. capitis infective endocarditis among 190 patients. All were male with an average age of 70.25 years (range, 58–80 years). The four cases were PVE: 3 aortic (1 mechanical and 2 biological bioprostheses) and 1 mitral (bioprosthesis). Their mean Euroscore II was 32.43 (range, 9.19–50.8). Three patients had underlying diseases (diabetes mellitus = 2, chronic obstructive pulmonary disease = 3, chronic kidney disease = 1, peripheral arterial disease = 2, ischemic heart disease = 1, dilated cardiomyopathy = 1). Preoperative clinical presentation was characterized by the occurrence of sepsis in three patients and heart failure and sepsis in one patient. Two patients presented with vegetation (mitral bioprosthesis, aortic bioprosthesis). A prosthetic dehiscence was present in all patients, and two presented with a localized annular abscess. All but one patient received triple antibiotic treatment with vancomycin plus rifampicin plus gentamycin. Surgery was performed on an urgent basis in all patients, and the in-hospital mortality rate was 50%. Conclusions: While limited by the small number of patients, our series highlights the aggressive clinical course of S. capitis PVE with a mortality rate close to that of Staphylococcus aureus PVE. Therefore, early surgical management is recommended to improve the clinical outcome of this serious disease.